Strengthening Islamic Moderation in Indonesia - Syukur, Yanuardi (Jurnal Pendidikan Islam, 2025)
Islamic moderation in Indonesia aims to create an Indonesian society that is religious and tolerant in a pluralistic society. This article explains an anthropologist’s reflection on religious moderation implemented in Indonesia to create a moderate society. This article aims to explain an anthropologist’s reflection on the Islamic moderation program in Indonesia which is indirectly included in the religious moderation of the Ministry of Religious Affairs of Republic of Indonesia. Practically, this reflection is useful to see how the Islamic moderation program is viewed from anthropological perspective. This article was using observations, participant observation and literature review. The author has been involved in various research programs in order to strengthening Islamic moderation in Indonesia. This article concludes that Islamic moderation in Indonesia is a necessity amidst the dynamics of global society. Practical strengthening of moderation is part of love for the Indonesian nation. However, this program will not run optimally unless it is through sustainable collaboration between the government, religious leaders, community leaders, youth and families.